15.7k views
5 votes
19. Solve the equation 3(x - 7) = 42.
• A. 21
B. 49
C. 36
D.7

2 Answers

1 vote

Answer:

The correct answer is option A. 21

Explanation:

It is given an expression in variable x, 3(x - 7) = 42

To find the value of x

Let 3(x - 7) = 42

3x - (3 * 7) = 42 (Open the bracket)

3x - 21 = 42

3x = 42 + 21

3x = 63

x = 63/3 = 21

Therefore the value of x = 21

The correct answer is option A. 21

User Wnnmaw
by
5.7k points
1 vote

For this case we must solve the following equation:


3 (x-7) = 42

Applying distributive property to the terms within the parenthesis we have:


3x-21 = 42

Adding 21 to both sides of the equation:


3x = 42 + 21\\3x = 63

Dividing between 3 on both sides of the equation:


x = \frac {63} {3}\\x = 21

Answer:


x = 21

User Zakaria Acharki
by
5.9k points